2022
DOI: 10.1108/mrr-06-2021-0430
|View full text |Cite
|
Sign up to set email alerts
|

Working role of women in a pandemic world: a poetic inquiry

Abstract: Purpose The sudden outbreak of the COVID-19 pandemic has affected millions of people globally, and it has exacerbated the existing gender inequalities that have affected women. The purpose of this study is to understand the perceptions of women concerning gender inequality in the workplace during the current pandemic. The goal is to give women a voice so they can explain their feelings regarding the problems they face in a pandemic world. Design/methodology/approach In this study, four poetic inquiries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although we tried to capture some variables, which address life-circumstances and the respective changes during the pandemic, our study did not target these in depth. It seems, for example, likely that higher demands in childcare and the resulting increases in workload might have led to variations in the experience of time and disparities between men and women, since numerous studies revealed that the decrease in childcare at home due to the discontinuation of childcare facilities and schools during the pandemic was largely shouldered by women (e.g., [ 40 – 42 ]). This seems relevant for the experience of time since previous research also revealed that parents report a faster passage of time compared to adults without children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we tried to capture some variables, which address life-circumstances and the respective changes during the pandemic, our study did not target these in depth. It seems, for example, likely that higher demands in childcare and the resulting increases in workload might have led to variations in the experience of time and disparities between men and women, since numerous studies revealed that the decrease in childcare at home due to the discontinuation of childcare facilities and schools during the pandemic was largely shouldered by women (e.g., [ 40 – 42 ]). This seems relevant for the experience of time since previous research also revealed that parents report a faster passage of time compared to adults without children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extended working hours and being "always on" make it hard for employees to get away from work both physically and mentally, which may cause work-related stress and time pressures that could impair the quality of personal life. Previous studies (de Gennaro et al, 2022;Kossek et al, 2021;Tayal & Mehta, 2022) presented experimental evidence on how WFH creates a conflict between work and personal life, especially for those with children. Our findings on work-life balance during WFH provide additional support.…”
Section: Alya (Activity-based Office Post-pandemic)mentioning
confidence: 99%
“…[5] stated that the COVID-19 pandemic has caused an increase in major depression and anxiety disorders among women due to the social and economic impacts they have experienced. The pandemic causes both men and women to endure psychological symptoms, but women are more likely than males to develop anxiety and sadness [6]. [7] defined anxiety as a low level of pleasure and high mental arousal.…”
Section: Introductionmentioning
confidence: 99%